Implementasi Metode Talqin dalam Program Tahfidz AlQur'an di Sekolah Menengah Pertama 31 Padang - Alqori Luthfi; Rahmi Wiza (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Until now, there are so many people who want to memorize the Koran, it's just that they still lack motivation, especially external motivation, so support from various parties is needed. In an effort to motivate and encourage students to memorize the Quran, junior high school 31 Padang as a leading public school in the city of Padang organizes student religious development activities in the form of tahfidz. The purpose of this study was to determine the implementation of the talqin method in the tahfidz Quran program at 31 Padang Junior High School. The research method used is a qualitative method with the type of field research (field research). Researchers act as research instruments. Data collection techniques used are in the form of observation and documentary. Meanwhile, the data analysis that the researcher uses is the analysis model of Milles and Huberman (1994) which is often called the interactive data analysis method with three stages, namely data reduction, data display and conclusion drawing or verification. The results of this study indicate that using the talqin method can make it easier for students to learn and memorize. This is evident from the memorization of students who already have memorized 1,3,5 chapters and some have even memorized 11 chapters.